Querying Variants: Boccaccio's 'Commedia' and Data-Models. Issue 1 (20th September 2019) - Tempestini, Sonia; Spadini, Elena
Abstract : This paper presents the methodology and the results of an analytical study of the three witnesses of Dante's Commedia copied by Giovanni Boccaccio, focusing on the importance of their digital accessibility. These extraordinary materials allow us to further our knowledge of Boccaccio's cultural trajectory as a scribe and as an author, and could be useful for the study of the textual tradition of Dante's Commedia . In the first section of the paper, the manuscripts and their role in previous scholarship are introduced. A thorough analysis of a choice of variants is then offered, applying specific categories for organizing the varia lectio. This taxonomy shows how fundamental it is to combine the methodological tools for studying copies (as usual in medieval philology) and those for studying author's manuscripts (as usual in modern philology) in dealing with the three manuscripts of Boccaccio's Commedia : in fact, the comparative analysis of the three manuscripts has much to reveal not only of their genetic relationship but also of Boccaccio's editorial practices. Furthermore, the analytic categories inform the computational model behind the web application 'La Commedia di Boccaccio', <http://boccacciocommedia.unil.ch/ > created for accessing and querying the variants. The model, implemented in a relational database, allows for the systematic management of different features of textual variations, distinguishing readings and their relationships, without setting a base text. The paper closes on a view to repurposing the model for handling other textual transmissions, working at the intersection between textual criticism and information technology.